-7=5(х+5) 9=5(х+9)7(х-1)=3х9(х+7)=-х5(х-3)=4х4(х+6)=х-х=4(6+х)7(-3+2х)=-6х+2

-7=5(х+5) 9=5(х+9) 7(х-1)=3х 9(х+7)=-х 5(х-3)=4х 4(х+6)=х -х=4(6+х) 7(-3+2х)=-6х+2
Гость
Ответ(ы) на вопрос:
Гость
-7 = 5(х+5)                                                                                                                        -7 = 5х+25                                                                                                                        -5х = 25+7                                                                                                                        -5х = 32                                                                                                                             х = 32:5                                                                                                                             х = 6.4
Не нашли ответ?
Ответить на вопрос
Похожие вопросы